PELAKSANAAN STANDAR PENYAMBUTAN TAMU OLEH RESEPSIONIS DI PRIME PARK HOTEL PEKANBARU - Ilda Safhira Rachman; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The hotel's front office or front office department is the main part of the hotel, because the front office department is an information center for guests. There are several sections in the front office, namely bell boy, bell drive, reception, and night audit. The reception is the first place guests will meet. The receptionist must give a good impression to every guest who comes to the hotel. This research was conducted at Prime Park Hotel Pekanbaru. Prime Park Hotel Pekanbaru is one of the 4 star hotels in Pekanbaru. In welcoming guests at Prime Park Hotel Pekanbaru, they already have good and correct standards from the start of preparation, the process of welcoming guests, and the services provided by the receptionist in welcoming guests. The receptionist plays an important role in welcoming guests. This study aims to determine the implementation of the receptionist in welcoming guests. This study uses a qualitative method with a descriptive approach, data collection techniques in this study using observation, documentation, interviews so that a very clear picture can be obtained. Informants in this study were Ast fom and receptionist at Prime Park Hotel Pekanbaru. Based on research, it shows that the standard of welcoming guests by the receptionist at Prime Park Hotel Pekanbaru is quite good, it's just that an inadequate number of employees makes many receptionist tasks hampered. Keywords : Reception, Welcoming Guest, Hotel